2022
DOI: 10.1155/2022/5719077
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Sequencing Reveals CXCR4 and IGF1 Behave Different Roles in Weightlessness Osteoporosis

Abstract: Objective. This study is aimed at screening the differential expression profiles of mRNA under weightlessness osteoporosis through high-throughput sequencing technology, as well as investigating the pathogenesis of weightlessness osteoporosis at the molecular level especially in bone marrow mesenchymal stem cells (BMSCs). Methods. The mouse bone marrow mesenchymal stem cell line was divided into ground group and simulated microgravity (SMG) group. BMP-2 was used to induce osteogenic differentiation, and SMG gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…The cost of treating and preventing further bone loss in Australians with osteoporosis or osteopenia is approximately $830 million or 30% of this 4,5 . It is indicated that osteoporosis will become a worldwide problem in the future 6 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cost of treating and preventing further bone loss in Australians with osteoporosis or osteopenia is approximately $830 million or 30% of this 4,5 . It is indicated that osteoporosis will become a worldwide problem in the future 6 …”
Section: Introductionmentioning
confidence: 99%
“…3 The cost of treating and preventing further bone loss in Australians with osteoporosis or osteopenia is approximately $830 million or 30% of this. 4,5 It is indicated that osteoporosis will become a worldwide problem in the future. 6 According to Pouresmaeili, there are risk factors for diseases involving bone formation pathways and osteoporosis fractures.…”
Section: Introductionmentioning
confidence: 99%